A modifiable universal cotinine-chimeric antigen system of NK cells with multiple targets - Kang, Hee Young; Lee, Soo Yun; Kim, Hyun Min; Lee, Su Ui; Lee, Hyunseung; Cho, Mi Young; Oh, Se-Chan; Kim, Seok-Min; Park, Hye Sun; Han, Eun Hee; Kim, Seong-Eun; Kim, Hyori; et al. (Frontiers in Immunology, 2023)
Natural killer (NK) cells are immune effector cells with outstanding features for adoptive immunotherapy. Immune effector cells with chimeric antigen receptors (CARs) are promising targeted therapeutic agents for various diseases. Because tumor cells exhibit heterogeneous antigen expression and lose cell surface antigen expression during malignant progression, many CARs fixed against only one antigen have limited efficacy and are associated with tumor relapse. To expand the utility of CAR-NK cells, we designed a split and universal cotinine-CAR (Cot-CAR) system, comprising a Cot-conjugator and NK92 cells (α-Cot-NK92 cells) engineered with a CAR containing an anti-Cot-specific single-chain variable fragment and intracellular signaling domain. The efficacy of the Cot-CAR system was assessed in vitro using a cytolysis assay against various tumor cells, and its single- or multiple- utility potential was demonstrated using an in vivo lung metastasis model by injecting A549-Red-Fluc cells. The α-Cot-NK92 cells could switch targets, logically respond to multiple antigens, and tune cytolytic activation through the alteration of conjugators without re-engineering. Therefore the universal Cot-CAR system is useful for enhancing specificity and diversity of antigens, combating relapse, and controlling cytolytic activity. In conclusion, this universal Cot-CAR system reveals that multiple availability and controllability can be generated with a single, integrated system.